COMPUTER MODELING OF CASTING PROCESSES USING CHARACTERISTICS OF POLYURETHANE BINDING AGENT OF SYSTEM Cold-Box-Amin - D. M. Kukij; A. P. Melnikov; A. V. Cherapovich; V. L. Akulich (Литьë и металлургия)
It is shown that using of data on thermo-decomposition of binding component will help to develop foundry technology with optimal characteristics.